GAMBARAN WORK-LIFE BALANCE PADA JAKSA WANITA YANG TELAH BERKELUARGA - Iwinda Pratama Hae; Ratriana Y.E. Kusumiati (Universitas Negeri Medan, 2020)
Married women who are working will encounter double roles. Participants in this study involve married female prosecutors having a family and children. Based on the initial interview with the participants, the prosecutors has a long responsibility starts from the investigation process with the police department, witness interrogation, case analysis and making the lawsuit, until the process of transferring the lawsuit to the court and convincing the judge with the lawsuit. Finally, the prosecutors also take an action in executing the criminals. They sometimes confront with the system problem versus their conscience which causes job stress and it influences on their family or they are on the conflict situation. However, there is also an enhancement situation; the job gives a positive advantage to the participants. The purpose of this study is to get the description of work-life balance on married female prosecutors having a family. The method used in this study is qualitative with the phenomenology approach of collecting data is by interview. There are 5 main themes in this study, such as job, family, experience of work-life balance, strategy and balance achievement. The result of this study shows that having double roles or experience of work-life balance, both participants experience similar conflict dynamics and enhancement orexperience ofwork-life balance. Both participants also make a perception that theyhave been in balance so far. They keep trying to be professional in working and also to spare their time be with their family. Keywords: Work-Life Balance, Conflict, Enhancement, Female Prosecutors, Married